EFFECT OF EARNING PER SHARE, CURRENT RATIO, DEBT TO l EQUITY RATIO IN PREDICTING FINANCIAL DISTRESS IN MINING COMPANIESl - Sri Ratnasari Harita; Wirda Lilia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
This study aims to determine and test the effect of partial or simultaneous Earning Per Share, Current Ratio, andDebt to Equity Ratio on Financial Distress in Mining Companies Listed on the Indonesia Stock Exchange. Thesampling technique uses purposive sampling technique, amounting to 14 companies with 4 years of observation.(four) years and data obtained from the financial statements of Mining Companies Listed on the Indonesia StockExchange at www.idx.co.id. The data analysis method used multiple linear regression analysis. Based on theresearch results, it is found that partially and simultaneously Earning Per Share, Current Ratio, and Debt toEquity Ratio have a significant effect on Financial Distress in Mining Companies Listed on the Indonesia StockExchange. The effect of Earning Per Share, Current Ratio, and Debt to Equity Ratio on Financial Distress inMining Companies Listed on the Indonesia Stock Exchange is 53.9%